Evaluation of ceramics adsorption filter as a pretreatment for seawater reverse-osmosis desalination - Wang, Jingwei (2023)
Seawater reverse osmosis (SWRO) is the most energy-efficient process for desalination to produce drinking water from seawater. However, its sustainability is still challenged by membrane fouling. Appropriate feed water quality is one of the crucial prerequisites for SWRO operation. In the current study, a ceramic adsorption filter (CAF), which was predominantly coated with an aluminum-based adsorbent (i.e., Alumina, Al2O3), was employed to enhance the pretreatment performance of SWRO. The fouling performance of SWRO pre-treated with a CAF was evaluated by feeding with real ultrafiltration (UF)-filtrated seawater collected from a seawater desalination R&D facility in Singapore. The flux decline profile showed that the presence of CAF after UF could mitigate around 10-30% of SWRO fouling. Based on the autopsy of the fouled SWRO membranes, it was observed that SWRO with CAF pre-treatment and daily regeneration could alleviate around 77.5% of Ca-induced inorganic fouling as well as 76% of lower biofouling. The present work highlights the potential of applying adsorption technology to enhance pre-treatment performance to extend the lifespan of SWRO membranes. Coupling the adsorbents on a ceramic filter should be a useful way to ease their implementation, i.e., inline adsorption and re-generation.